2017
DOI: 10.1007/s11999-016-4761-z
|View full text |Cite
|
Sign up to set email alerts
|

What Is the Expected Learning Curve in Computer-assisted Navigation for Bone Tumor Resection?

Abstract: Background Computer navigation during surgery can help oncologic surgeons perform more accurate resections. However, some navigation studies suggest that this tool may result in unique intraoperative problems and increased surgical time. The degree to which these problems might diminish with experience-the learning curve-has not, to our knowledge, been evaluated for navigation-assisted tumor resections. Questions/purposes (1) What intraoperative technical problems were observed during the first 2 years using n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
37
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(38 citation statements)
references
References 20 publications
(43 reference statements)
1
37
0
Order By: Relevance
“…For computerized navigation, one study demonstrated that after 2 years, the intraoperative time decreased yet registration error did not improve. 31 For pelvic PSIs, some authors report that the guide was consistently situated within 5 minutes 15 and that the learning curve for using PSIs was 10 cases. 32 Operations using PSI technology may prove to be faster than computerized navigation in pelvic resections 11 and freehand techniques in total knee arthroplasties.…”
Section: Resultsmentioning
confidence: 99%
“…For computerized navigation, one study demonstrated that after 2 years, the intraoperative time decreased yet registration error did not improve. 31 For pelvic PSIs, some authors report that the guide was consistently situated within 5 minutes 15 and that the learning curve for using PSIs was 10 cases. 32 Operations using PSI technology may prove to be faster than computerized navigation in pelvic resections 11 and freehand techniques in total knee arthroplasties.…”
Section: Resultsmentioning
confidence: 99%
“…Surgical precision, understood as the correspondence between a target osteotomy and an executed osteotomy, is not the only factor to consider when evaluating navigation-assisted surgery. Some complications associated with intraoperative navigation, such as increased procedure time or uncompleted navigation due to technical problems, have shown to decrease as the surgeon team familiarizes with the technology (increasing their total amount of surgeries performed under navigation) [19]. On the contrary, the accuracy level in the registration process appears to be independent of the learning curve and not decreasing with user experience.…”
Section: Discussionmentioning
confidence: 99%
“…Preoperative three-dimensional (3-D) planning of the osteotomy may have implications not only for the adequacy of the resection margins, but also for the biomechanical stability and design of the prosthesis [3][4][5][6]. The difficulty remains in how we transfer insights of the preoperative 3-D planning process to the operating field.…”
Section: How Do We Get There?mentioning
confidence: 99%
“…The difficulty remains in how we transfer insights of the preoperative 3-D planning process to the operating field. We have two options if we wish to reproduce this planning in the operative room and increase accuracy: (1) Computer-assisted navigation technologies [3,6] or (2) Patient-specific templates that make a guided osteotomy feasible [4,5].…”
Section: How Do We Get There?mentioning
confidence: 99%
See 1 more Smart Citation